Gender-Based Violence and Health Justice: Addressing the Impact of Violence on Women’s Health in Indonesia (Indonesian Health Justice Review, 2025)
Gender-based violence (GBV) remains a pervasive issue in Indonesia, with profound implications for women’s physical and mental health. This paper explores the relationship between GBV and health justice, examining the ways in which violence against women impacts their access to healthcare, mental well-being, and overall quality of life. Using qualitative research methods, including interviews with survivors, healthcare providers, and women’s rights advocates, the study reveals that women who experience GBV face significant barriers in accessing appropriate health services, including inadequate mental health care, physical health support, and legal protection. The paper argues that addressing GBV is essential for achieving health justice, as the health system must be responsive to the specific needs of survivors. It also highlights the intersectionality of GBV with other forms of inequality, such as economic vulnerability and lack of education, which further compound health disparities. The paper concludes with policy recommendations for improving healthcare responses to GBV, including training healthcare professionals in trauma-informed care, providing better support services for survivors, and strengthening legal protections. The study emphasizes the need for a coordinated approach that integrates health, legal, and social services to address GBV and promote health justice for women in Indonesia.